2005
DOI: 10.1158/0008-5472.can-04-3617
|View full text |Cite
|
Sign up to set email alerts
|

An Expression-Based Site of Origin Diagnostic Method Designed for Clinical Application to Cancer of Unknown Origin

Abstract: Gene expression profiling offers a promising new technique for the diagnosis and prognosis of cancer. We have applied this technology to build a clinically robust site of origin classifier with the ultimate aim of applying it to determine the origin of cancer of unknown primary (CUP). A single cDNA microarray platform was used to profile 229 primary and metastatic tumors representing 14 tumor types and multiple histologic subtypes. This data set was subsequently used for training and validation of a support ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
144
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(156 citation statements)
references
References 49 publications
2
144
0
1
Order By: Relevance
“…Cilia are present in normal adult ovarian surface epithelium (57) and commonly observed in benign and LMP tumor cells (58). Previous literature has suggested retention of some basic expression pattern from the cell of origin to tumor tissue and even cell lines (59,60); this may represent the gene expression pattern from a relatively well-differentiated ovarian surface epithelial cell. Although invasive serous tumors are also thought to arise from the ovarian surface epithelium, most lack expression of this Dynein cluster.…”
Section: Discussionmentioning
confidence: 95%
“…Cilia are present in normal adult ovarian surface epithelium (57) and commonly observed in benign and LMP tumor cells (58). Previous literature has suggested retention of some basic expression pattern from the cell of origin to tumor tissue and even cell lines (59,60); this may represent the gene expression pattern from a relatively well-differentiated ovarian surface epithelial cell. Although invasive serous tumors are also thought to arise from the ovarian surface epithelium, most lack expression of this Dynein cluster.…”
Section: Discussionmentioning
confidence: 95%
“…38,39 Recent work suggested the use of large panels of mRNA features for identification of tumor tissue of origin. 9,10,14,15 Our test uses a significantly smaller number of tissue-specific microRNA biomarkers, set forth in a straightforward classification scheme, which provides specific tissue origins in a majority of cases. Cases with consensus classifications are accurately identified with a higher confidence.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Most studies of molecular diagnosis of tissue of origin used messenger RNA (mRNA) profiling of tumor samples. 8,[13][14][15] MicroRNAs, 21-23-nucleotide-long functional RNAs, have an important function in tissue differentiation 16,17 and tumorigenesis, 18,19 and have highly tissue-specific expression patterns. [20][21][22] The unique expression profiles of microRNAs characteristic of each tissue and the malignancies arising in them can permit their accurate identification.…”
mentioning
confidence: 99%
“…Recently, several independent studies have demonstrated proof of principle for the use of gene expression microarrays (GEMs) in identifying a foster primary site for CUP (Giordano et al, 2001;Ramaswamy et al, 2001;Su et al, 2001;Dennis et al, 2002;Buckhaults et al, 2003;Shedden et al, 2003;Bloom et al, 2004;Tothill et al, 2005) Data from GEM of known primary tumours have been examined 'blindly' and the correct primary site identified with up to 89% accuracy. The success of these studies demonstrates that patterns of gene expression remain consistent with tissue of origin, both in cell lines (Ross et al, 2000) and tumour samples (Khan et al, 2001).…”
mentioning
confidence: 99%